Study of water based on physicochemical analysis (Eurasian Research Bulletin, 2023)
Water is a fundamental molecule that plays a critical role in sustaining life and supporting biochemical processes on Earth. This scientific study aims to uncover the intricate physical and chemical properties of water through an extensive analysis. By employing various sophisticated techniques, including spectroscopy, chromatography, and elemental analysis, this investigation explores the structure, behavior, and essential characteristics of water. The findings contribute to a deeper understanding of water's importance across various fields, including biology, ecology, and environmental science.